Older people and mental health nursing : a handbook of care - Neno, Rebecca; Aveyard, Barry; Heath, Hazel B. M. (Blackwell Pub., 2007)
Older people and mental health nursing provides an evidence-based guide to caring for the growing number of older people with mental health issues. It focuses on the knowledge and key skills which practitioners require to work effectively with older people who have, or are at risk of developing, mental health needs.